The Economic Impact of Space Weather: Where Do We Stand?. Issue 2 (23rd February 2017) - Eastwood, J. P.; Biffis, E.; Hapgood, M. A.; Green, L.; Bisi, M. M.; Bentley, R. D.; Wicks, R.; McKinnell, L.‐A.; Gibbs, M.; Burnett, C.
Abstract : Space weather describes the way in which the Sun, and conditions in space more generally, impact human activity and technology both in space and on the ground. It is now well understood that space weather represents a significant threat to infrastructure resilience, and is a source of risk that is wide‐ranging in its impact and the pathways by which this impact may occur. Although space weather is growing rapidly as a field, work rigorously assessing the overall economic cost of space weather appears to be in its infancy. Here, we provide an initial literature review to gather and assess the quality of any published assessments of space weather impacts and socioeconomic studies. Generally speaking, there is a good volume of scientific peer‐reviewed literature detailing the likelihood and statistics of different types of space weather phenomena. These phenomena all typically exhibit "power‐law" behavior in their severity. The literature on documented impacts is not as extensive, with many case studies, but few statistical studies. The literature on the economic impacts of space weather is rather sparse and not as well developed when compared to the other sections, most probably due to the somewhat limited data that are available from end‐users. The major risk is attached to power distribution systems and there is disagreement as to the severity of the technological footprint. This strongly controls the economic impact. Consequently, urgent work is required to better quantify the risk of future space weather events.